The canonical dimension of the title of doctor of the Church about the possible conferral of this title on Saint Caesar of Arles - Tourneau, Dominique (Prawo Kanoniczne, 2020)
In his article, the author presents the canonical criteria for con- ferring the title of Doctor of the Church in the historical perspective. In this context, he presents the life and achievements of St. Caesar of Arles in view of possible conferring on him the title of Doctor of the Church. Despite the current tendency to limit such nominations, the author emphasizes two reasons for a possible nomination: first, his achievements in the field of canon law, and second, some other criteria that Saint Caesar of Arles meets to initiate the procedure of conferring on him such a title.